Islamization of Science as a Paradigm for Integrating Science and Religion in Contemporary Islamic Education - Agung Agus Revaldo (JISEI: Journal of Islamic Studies and Educational Innovation, 2026)
Contemporary Islamic education currently faces major challenges in the form of increasingly rapid developments in science and technology, as well as the separation between religious knowledge and general knowledge, known as the dichotomy of knowledge. This condition causes students to tend to view religious knowledge and general knowledge as two different and unrelated things. Therefore, an educational concept is needed that can integrate both knowledge so that Islamic education can run in a balanced and relevant manner to current developments. This study aims to determine the concept of the Islamization of knowledge and its relevance to contemporary Islamic education. This study uses a qualitative method with a library research approach. Data sources were obtained from books, scientific journals, articles, and various references related to the Islamization of knowledge and contemporary Islamic education. Data collection techniques were carried out through documentation and literature studies, while data analysis used qualitative descriptive analysis. The results of the study indicate that the Islamization of knowledge is an effort to connect knowledge with Islamic values ​​so that knowledge is not separated from religious teachings and humanitarian goals. The concept of the Islamization of knowledge was developed by figures such as Syed Muhammad Naquib Al-Attas and Ismail Raji Al-Faruqi, who emphasized the importance of integration between religious knowledge and general knowledge. In contemporary Islamic education, the Islamization of knowledge has very important relevance because it can help form students who are not only intellectually superior, but also have faith, noble morals, and the ability to face modern challenges. The implementation of Islamization of knowledge can be carried out through curriculum integration, contextual learning, and connecting religious material with science and technology. Thus, the Islamization of science can be one solution in developing Islamic education that is more comprehensive, balanced and in line with current developments.